2023
DOI: 10.1186/s13002-023-00579-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study on herbal tea drinks in Guangxi, China

Abstract: Background Herbal tea drinks, different from classical Camellia beverages, are a wide variety of herbal drinks consumed for therapeutic purposes or health promotion. Herbal tea is widely consumed in Guangxi. However, the documentation on the plants for herbal tea and their related health benefits is still limited. Methods An ethnobotanical survey was conducted in 52 villages and 21 traditional markets in Guangxi from 2016 to 2021. Semi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Sarcandra glabra, Centella asiatica, and Gynostemma pentaphyllum are the most commonly available plants used for making Liáng chá. Similar findings can also be found in the "Ethnobotanical study on herbal tea drinks in Guangxi, China" [37]. Some vendors prepare Centella asiatica with added sugar to create a refreshing tea beverage, which is sold at a price of 10 yuan per cup.…”
Section: Tea Substitutessupporting
confidence: 77%
“…Sarcandra glabra, Centella asiatica, and Gynostemma pentaphyllum are the most commonly available plants used for making Liáng chá. Similar findings can also be found in the "Ethnobotanical study on herbal tea drinks in Guangxi, China" [37]. Some vendors prepare Centella asiatica with added sugar to create a refreshing tea beverage, which is sold at a price of 10 yuan per cup.…”
Section: Tea Substitutessupporting
confidence: 77%
“…Chinese traditional medicine theory believes that traditional Chinese herbal supplements positively affect health promotion. In some regions of China, there is a widespread habit of consuming Chinese herbal supplements (including drinking herbal tea), and some research has shown that these habits have a high level of acceptance among the local population [ 28 , 29 ]. However, these health-protective effects from traditional Chinese herbal supplements are often considered preliminary because of the potential effectiveness of placebos [ 30 ] and the lack of validation from long-term, large-scale cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of this medicinal plant contain several saponins, polysaccharides, flavonoids, phytosterols and other bioactive ingredients that effectively act as anti-cancer and anti-atherogenic agents as well as affording neuroprotective and hepatoprotective properties ( Su et al., 2021 ). Apart from its use in traditional Chinese medicine, G. pentaphyllum leaves are also utilized in tea production ( Long et al., 2023 ). Due to its diverse range of applications, G. pentaphyllum has been praised as “southern ginseng” in China.…”
Section: Introductionmentioning
confidence: 99%